2020
DOI: 10.2147/dmso.s289642
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of IGF2BP2 rs4402960 Variant, Smoking and Type 2 Diabetes

Abstract: Purpose: Genetic and environmental factors are related to type 2 diabetes (T2D). Genetic modifiers of T2D have not been widely determined among smoking individuals. In this population-based study, we investigated the interactive association between rs4402960 polymorphism of the insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) gene and smoking with T2D among Taiwanese adults. Materials and Methods: We obtained genetic data collected between 2008 and 2018 for 22,039 participants (aged 30-70 years) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Benrahma et al observed a significant correlation between IGF2BP2 rs4402-960 polymorphism and diabetes under additive 2 and recessive models ( 23), but in a previous report in a Moroccan population, Saxena et al stated that there was no association of this SNP with diabetes (p = 0.22) (24). Additionally, the T allele frequency was 37.66% in controls, like the frequency found in South Asians (32%), Europeans (31%), and East Asians (28%); the maximum incidence (49%) was observed in an African population (3,23). Moreover, several types of research tried to clarify the connection between IG-F2BP2 rs4402960 variants and diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…Benrahma et al observed a significant correlation between IGF2BP2 rs4402-960 polymorphism and diabetes under additive 2 and recessive models ( 23), but in a previous report in a Moroccan population, Saxena et al stated that there was no association of this SNP with diabetes (p = 0.22) (24). Additionally, the T allele frequency was 37.66% in controls, like the frequency found in South Asians (32%), Europeans (31%), and East Asians (28%); the maximum incidence (49%) was observed in an African population (3,23). Moreover, several types of research tried to clarify the connection between IG-F2BP2 rs4402960 variants and diabetes.…”
Section: Discussionmentioning
confidence: 87%
“…Insulin secretion, which is essential for glucose metabolism, is regulated by the IGF2BP2 gene. rs4402960 and rs1470-579 that we investigated are the most widely studied polymorphisms of this gene and yielded both solid and weak or no associations with T2DM (3,4).…”
Section: Introductionmentioning
confidence: 88%
“…IGF2BP2 belongs to an RNA-binding protein that is a postqualitative regulator of messenger RNA (mRNA) localization, stability, and conversion control 9 . Current research shows that the IGF2BP2 gene is related to the occurrence and development of diabetes [10][11][12] . IGF2BP2 is a key gene in the m6A signaling pathway and has recently been shown to play a role in the occurrence and development of various cancers [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%